The contribution of achievement motivation toward student study skill - Birrul Walidaini; Neviyarni Neviyarni; Rusdinal Rusdinal (International Conferences on Educational, Social Sciences and Technology)
Study skill is the skill acquired by training student and learning can Enhance independence. In fact, there are many students who have not good study skill. Achievement motivation is one of the factors that prediction students study skill. The purpose of this research is to examine the contribution of achievement motivation toward study skill. This research used quantitative with descriptive correlation method. The population of this research is 625 and 244 samples of guidance and counseling majors students, UniversitasNegeri Padang. The instruments of the research used the Likert scale model, value of reliability are 0.841 and 0.842. The Data were Analyzed with simple regression. The result of this research shows that there is a contribution (25.2%) of achievement motivation toward study skill.